2012
DOI: 10.1177/0040517512445340
|View full text |Cite
|
Sign up to set email alerts
|

Tensile mechanics of braided sutures

Abstract: Sutures are the materials primarily used for closing wounds, and their performance is significantly dependent on their mechanical characteristics. Thus, their tensile property is a key parameter responsible for the success of a suture. In this paper, a simple analytical tensile model of braided sutures has been developed based on braid geometry, braid kinematics, and constituent monofilament properties. The model has accounted for the changes in the braid geometry, including braid angle, diameter, and Poisson’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…Indeed, a rise in the CR corresponds to a decrease in the braiding angle. This is clearly shown in Table 3 and it was also reported by Alpyildiz, who studied the geometry of tubular braids, and Rawal et al, who studied mechanical properties of braided sutures [28,29]. …”
Section: Effect Of the Manufacturing Parameters On The Braided Prosthsupporting
confidence: 75%
“…Indeed, a rise in the CR corresponds to a decrease in the braiding angle. This is clearly shown in Table 3 and it was also reported by Alpyildiz, who studied the geometry of tubular braids, and Rawal et al, who studied mechanical properties of braided sutures [28,29]. …”
Section: Effect Of the Manufacturing Parameters On The Braided Prosthsupporting
confidence: 75%
“…For the bi-axial overbraided sleeve, which is modelled as an orthotropic shell, the homogenisation procedure for the elastic properties of over-braided sleeves is relatively complicated as the properties of the braid will be different from the properties of the individual fibre tows used to produce the braid architectures. There are several experimental and analytical studies conducted on braided structures [19][20][21][22][23], especially with regard to biaxial braided sleeves with and without a core. However, none of them can directly be employed to predict homogenised properties that can represent the over-braided sleeve as an equivalent orthotropic shell for the current multi-scale analysis.…”
Section: Multi-scale Modelling Methodologymentioning
confidence: 99%
“…The models also showed that the diameter of the braided structures decreases with increase in length. Rawal et al [11] studied the tensile properties of braided structures based on braid geometry, braid kinematics, and constituent monofilament properties, taking into account the changes in the braid geometry, including braid angle, diameter, and Poisson's ratio. They established that both the both braid angle and diameter are found to be critical design parameters to the model of jamming state of mono filaments.…”
Section: Introductionmentioning
confidence: 99%